The Neural Specificity of Movement Preparation During Actual and Imagined Movements. (4th January 2018) - Lebon, Florent; Ruffino, Célia; Greenhouse, Ian; Labruna, Ludovica; Ivry, Richard B; Papaxanthis, Charalambos
Abstract: Current theories consider motor imagery, the mental representation of action, to have considerable functional overlap with the processes involved in actual movement preparation and execution. To test the neural specificity of motor imagery, we conducted a series of 3 experiments using transcranial magnetic stimulation (TMS). We compared changes in corticospinal excitability as people prepared and implemented actual or imagined movements, using a delayed response task in which a cue indicated the forthcoming response. TMS pulses, used to elicit motor-evoked responses in the first dorsal interosseous muscle of the right hand, were applied before and after an imperative signal, allowing us to probe the state of excitability during movement preparation and implementation. Similar to previous work, excitability increased in the agonist muscle during the implementation of an actual or imagined movement. Interestingly, preparing an imagined movement engaged similar inhibitory processes as that observed during actual movement, although the degree of inhibition was less selective in the imagery conditions. These changes in corticospinal excitability were specific to actual/imagined movement preparation, as no modulation was observed when preparing and generating images of cued visual objects. Taken together, inhibition is a signature of how actions are prepared, whether they are imagined or actually executed.